Piratical Colonization: Piracy's Role in the First English Colonies, 1550-1600 - Croom, Austin F (East Carolina University, 2019)
This thesis analyzes the importance of piracy to the beginnings of English overseas expansion. This study will consider the piratical climate around the British Isles in the sixteenth century, and the ways in which this context affected the participants in the first English colonial projects. Piracy became inseparably associated with nearly all of the Elizabethan overseas expeditions, contributing experienced seamen to the cause and promising to fill gaps in the financial strength of the expeditions. Ultimately, piracy proved difficult to control, and sabotaged the efforts of the Elizabethan colonial promoters.
Keywords: England; early America; Piracy--British Isles--History--16th century; Colonies--History